2022
DOI: 10.1186/s12872-022-02754-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment and molecular mechanism of the upregulation of Toll-like receptor 2 (TLR2) in myocardial infarction

Abstract: Objective The prevalence and mortality of cardiovascular diseases remain ranked first worldwide. Myocardial infarction (MI) is the central cause of death from cardiovascular diseases, seriously endangering human health. The clinical implication of toll-like receptor 2 (TLR2) remains contradictory, and its mechanism is still unknown. Hence, the objective of this study was to elucidate the clinical value and molecular mechanism of TLR2 in MI. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…CD274 [175], CEACAM1 [176], STAT1 [177], ARG1 [178], TLR4 [179], LRRK2 [180], ABCA1 [181], IFIH1 [182], TLR5 [183], PTGS2 [184], CYP2D6 [185], RNF213 [186], C9ORF72 [187], JAK2 [188], TLR8 [189], NOTCH2 [190], PDGFC (platelet derived growth factor C) [191], TLR2 [192], PRKAB2 [193], HDAC9 [194], NCOA4 [195], LATS2 [196], DICER1 [197], IL1RN [198], GCH1 [148], EGR1 [199], HIPK3 [200], ZEB2 [201], HIF1A [202], PLA2G7 [203], DOCK8 [204], CCR2 [205], PPP1R15B [206], GCLC (glutamate-cysteine ligase catalytic subunit) [207], VEGFA (vascular endothelial growth factor A) [208], SORL1 [209], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [210], EIF2AK3 [211], SLC40A1 [212], PHLPP1 [213], IGF2R [214], LPIN2 [215], SIRT1 [216], VPS13C [217], ACSL4 [218], ELOVL6 [219], FGL2 [220], ERO1B [221], XAF1 [222], TET2 [223], TET3 [224], PF4 [225], POU2F1 [226], PC (pyruvate carboxylase) [227], NDUFS8 [228], PRDX2 [229], RUNX3 [230], HSPB1 [231], TCF4 [169], TCF7 [232], IGFBP4 [233], HSPG2 [234], NMRAL1 [173], AQP3 [235] and LGALS3 [236] might be a potential therapeutic target for diabetes mellitus. Studies have found that CEACAM1 [237], STAT1 [238], ARG1 [239], TLR4 [240], LRRK2 [241], ABCA1 [242], PTGS2 [243], CYP2D6 [244], JAK2 [245], TLR2 […”
Section: Discussionmentioning
confidence: 99%
“…CD274 [175], CEACAM1 [176], STAT1 [177], ARG1 [178], TLR4 [179], LRRK2 [180], ABCA1 [181], IFIH1 [182], TLR5 [183], PTGS2 [184], CYP2D6 [185], RNF213 [186], C9ORF72 [187], JAK2 [188], TLR8 [189], NOTCH2 [190], PDGFC (platelet derived growth factor C) [191], TLR2 [192], PRKAB2 [193], HDAC9 [194], NCOA4 [195], LATS2 [196], DICER1 [197], IL1RN [198], GCH1 [148], EGR1 [199], HIPK3 [200], ZEB2 [201], HIF1A [202], PLA2G7 [203], DOCK8 [204], CCR2 [205], PPP1R15B [206], GCLC (glutamate-cysteine ligase catalytic subunit) [207], VEGFA (vascular endothelial growth factor A) [208], SORL1 [209], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [210], EIF2AK3 [211], SLC40A1 [212], PHLPP1 [213], IGF2R [214], LPIN2 [215], SIRT1 [216], VPS13C [217], ACSL4 [218], ELOVL6 [219], FGL2 [220], ERO1B [221], XAF1 [222], TET2 [223], TET3 [224], PF4 [225], POU2F1 [226], PC (pyruvate carboxylase) [227], NDUFS8 [228], PRDX2 [229], RUNX3 [230], HSPB1 [231], TCF4 [169], TCF7 [232], IGFBP4 [233], HSPG2 [234], NMRAL1 [173], AQP3 [235] and LGALS3 [236] might be a potential therapeutic target for diabetes mellitus. Studies have found that CEACAM1 [237], STAT1 [238], ARG1 [239], TLR4 [240], LRRK2 [241], ABCA1 [242], PTGS2 [243], CYP2D6 [244], JAK2 [245], TLR2 […”
Section: Discussionmentioning
confidence: 99%
“…Besides, it has also been found that TLR2, together with NETs, may play a crucial role in plaque erosion through the induction of endoplasmic reticulum stress and apoptosis (34). Moreover, the upregulation of TLR2 may have a favorable screening value for AMI (35).…”
Section: Discussionmentioning
confidence: 99%
“…Early inflammation is beneficial for cardiac function as it removes necrotic material and heals the infarct area. However, excessive inflammation is detrimental as it contributes to ventricular arrhythmias and heart failure, thus resulting in high mortality in MI patients [89]. These studies highlight apoptosis, necrosis, inflammation, and fibrosis as the critical pathways in MI.…”
Section: Myocardial Infarctionmentioning
confidence: 99%